2019
DOI: 10.1111/evj.13127
|View full text |Cite
|
Sign up to set email alerts
|

Synovial sepsis of unknown origin in the adult Thoroughbred racehorse

Abstract: Summary Background Synovial sepsis of unknown origin is a rare cause of lameness in the adult horse, and a haematogenous pathogenesis has been proposed in previous cases. Objectives To describe the features and outcome of synovial sepsis of unknown origin in adult Thoroughbred racehorses. Study design Retrospective case series. Methods Hospital records for admissions between 2005 and 2015 were reviewed to identify adult horses diagnosed with synovial sepsis of unknown origin. Presentation, clinicopathological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
(94 reference statements)
1
3
0
Order By: Relevance
“…Within the equine literature, epidemiological studies specifically investigating causes of contaminated synovial structures and synovial sepsis are limited to studies on iatrogenic injury [19][20][21][22][23] and idiopathic causes. 24 There has been some research into risk factors for traumatic injuries occurring in horses The duration of time between injury and admission or treatment has been previously identified by two studies to be associated with poorer outcomes; 5,7 however, in the present study this was found to have no association with long-term survival consistent with other research. 3,9,11 The reason for these differences is unknown but may be because there are multiple factors that could affect the duration of time between the injury occurring and treatment being initiated.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Within the equine literature, epidemiological studies specifically investigating causes of contaminated synovial structures and synovial sepsis are limited to studies on iatrogenic injury [19][20][21][22][23] and idiopathic causes. 24 There has been some research into risk factors for traumatic injuries occurring in horses The duration of time between injury and admission or treatment has been previously identified by two studies to be associated with poorer outcomes; 5,7 however, in the present study this was found to have no association with long-term survival consistent with other research. 3,9,11 The reason for these differences is unknown but may be because there are multiple factors that could affect the duration of time between the injury occurring and treatment being initiated.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, detailed analysis and comparisons of the known causes of injury was not possible due to the small sample sizes. Within the equine literature, epidemiological studies specifically investigating causes of contaminated synovial structures and synovial sepsis are limited to studies on iatrogenic injury 19–23 and idiopathic causes 24 . There has been some research into risk factors for traumatic injuries occurring in horses previously 22 and, similarly, in 19% of cases the cause of injury was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…10 Monomicrobial, aerobic infections are the most common isolates in cases of haematogenous synovial sepsis. [11][12][13] O'Sullivan et al 2 isolated Staphylococcus intermedius from synovial fluid, consistent with bacterial species present in pathologic hoof tissue. 14 Our report documents the isolation of Bacteroides sp., a Gramnegative anaerobic bacteria.…”
Section: A C K N O W L E D G E M E N T Smentioning
confidence: 81%
“…While septic arthritis in horses is most commonly a result of penetrating traumatic injuries or iatrogenic following intrasynovial injections, idiopathic synovial sepsis typically also involving one joint has recently been described 13 18 19. In a case series involving 11 horses, the diagnosis of synovial sepsis was based on an elevated nucleated cell count, total protein and a neutrophil differential percentage of ≥80%, whereas the culture of a causative organism was successful in only 6 patients 19. In our patient, B. afzelii DNA was detected in the tarsocrural joint via PCR analysis although synovial culture yielded a negative result.…”
Section: Discussionmentioning
confidence: 99%